The Evolution of Bio-Mordant Research in Natural Textile Dyeing: A Bibliometric Study - Retnaini Nur Tafi'i; Adhi Kusumastuti (Universitas Negeri Semarang, 2026)
The growing global attention to sustainability has driven the development of environmentally friendly alternatives in textile dyeing processes, one of which is the utilization of bio-mordants as substitutes for metal mordants. Although experimental research on bio-mordants continues to expand, systematic mapping of trends, knowledge structures, and research directions in bio-mordant studies remains limited. Therefore, this study aims to comprehensively analyze the development of bio-mordant research in natural textile dyeing using a bibliometric approach. This study adopts the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, with data sourced from the Scopus database. A literature search using the keywords “bio” and “mordan*” yielded 329 documents, which, after screening and the application of inclusion criteria, resulted in 71 articles selected for further analysis. Bibliometric analysis was conducted using VOSviewer software to map publication trends, geographical distribution, institutional affiliations, author productivity, and keyword co-occurrence. The results indicate that bio-mordant research has experienced significant growth since 2020, reaching its peak in 2023, with publications predominantly originating from countries with strong textile industries. The main keywords identified reflect a close relationship between bio-mordants, natural dyes, color fastness, and sustainability. These findings highlight the theoretical and practical relevance of bio-mordants in supporting the transition toward more sustainable textile dyeing processes and provide opportunities for future research.